PENGARUH SUPERVISI AUDIT TERHADAP KUALITAS HASIL KERJA AUDITOR DENGAN TEKANAN PENGARUH SOSIAL SEBAGAI VARIABEL MODERATING: STUDI PADA AUDITOR EKSTERNAL PEMERINTAH - Razaq, Safri A. (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2013)
This study aimed to investigate the effect of social influence pressure on the relationshipbetween supervision and the quality of the work of the auditor. The study was conducted atthe government´s external auditor who worked on at the Audit Board of The Republic ofIndonesia (BPK) Aceh representative. The method used in this study is the census method, ieby taking all auditors working in the KPK which totaled 64 people. The data used areprimary data obtained through the distribution of questionnaires to the auditors and wereanalyzed using multiple linear regression models. The results showed that: (1) Supervisionpositive effect on the quality of audit work the auditor, (2) social influence pressuresnegatively affect the quality of the work of the auditor, and (3) the influence of social pressureaffect the relationship between supervision and the quality of the work of the auditor.Keywords: supervision, social influence pressures, the quality of the work of the auditor